2022
DOI: 10.23937/2474-3658/1510250
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of <em>Acinetobacter</em> Infections in COVID and Non-COVID Patients

Abstract: Background: Acinetobacter species are associated with high mortality, with A. baumannii being associated with a significant number of hospitals acquired infections worldwide. Multidrug resistance makes it challenging to control or treat these infections. Aim of this study is to evaluate the risk factors and compare the clinical outcomes of Acinetobacter infections in a tertiary care hospital, in COVID and non COVID patients. Materials and methods:A retrospective observational study was conducted. A list of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Several studies had already reported A. baumannii, P. stutzeri, and P. aeruginosa, as major causes of secondary infection in hospital admitted COVID-19 patients. 28 , 29 , 30 , 31 Moreover, the significant disruption of TAMs in Delta was persistent across clinical outcomes of recovery and mortality too. Delta mortality patients had a substantial presence of opportunistic bacterial species belonging to Acinetobacter, Enterococcus, Prevotella, and Streptococcus genera, which was lacking in the Pre-VOC and Omicron.…”
Section: Discussionmentioning
confidence: 95%
“…Several studies had already reported A. baumannii, P. stutzeri, and P. aeruginosa, as major causes of secondary infection in hospital admitted COVID-19 patients. 28 , 29 , 30 , 31 Moreover, the significant disruption of TAMs in Delta was persistent across clinical outcomes of recovery and mortality too. Delta mortality patients had a substantial presence of opportunistic bacterial species belonging to Acinetobacter, Enterococcus, Prevotella, and Streptococcus genera, which was lacking in the Pre-VOC and Omicron.…”
Section: Discussionmentioning
confidence: 95%
“…[49][50][51]. Nevertheless, an increased risk of Acinetobacter baumannii infections in non-critical COVID-19 patients is worrisome, given that the mortality associated with this etiologic agent has been reported to be as high as 85.7% [52].…”
Section: Discussionmentioning
confidence: 99%